The Role of Cytomegalovirus, Haemophilus Influenzae and Epstein Barr Virus in Guillain Barre Syndrome - Shahriar Nafissi; Zahra Vahabi; Maryam Sadeghi Ghahar; Ali Akbar Amirzargar; Soheil Naderi (Acta Medica Iranica, 2013)
Guillain Barre Syndrome (GBS) is an inflammatory, usually demyelinating, polyneuropathy; clinically characterized by acute onset of symmetric progressive muscle weakness with loss of myotatic reflexes. Thirty five patients with GBS, defined clinically according to the criteria of Asbury and Cornblath, were recruited from three hospital affiliated to Tehran University of Medical Sciences.As a control group 35 age and sex matched patients with other neurological diseases admitted to the same hospital at the same time, were included in our study. Serum samples were collected before treatment from each patient (within 4 weeks after the disease onset) and controls, and stored frozen at -80ºC until serologic assays were done. Serologic testing of pretreatment serum was performed in all patients. Positive titer of virus specific IgM antibody against cytomegalovirus (CMV) was found in 6 cases and 2 controls. 34 patients and 31 controls had high titer of anti Haemophilus influenzae IgG and one patient had serologic evidence of a recent Epstein Barr virus (EBV) infection. The mean titer of IgG antibody against Haemophilus influenzae in cases and controls was 5.21 and 2.97 respectively. Although serologic evidence of all these infections were more frequent in cases than in controls, only Haemophilus influenzae infection appeared to be significantly related to GBS (P=0.002). Eleven cases and 3 controls had high titers of IgG antibody against Haemophilus influenzae type B (titer >8). There is significant association between high titer of IgG antibody against Haemophilus influenzae and GBS (P=0.017). Our results provide further evidence that Haemophilus influenzae and probably CMV, can be associated with GBS.